Intestinal anisakiasis with severe intestinal ischemia caused by extraluminal live larvae: a case report - Kengo Shibata; Yuichi Yoshida; Yoichi Miyaoka; Shin Emoto; Tomoaki Kawai; Seiji Kobayashi; Kazuhiro Ogasawara; Akinobu Taketomi (Surgical Case Reports, 2020)
Abstract Background Anisakiasis is a parasitic infection caused by Anisakis worms found in raw fish. Most cases of anisakiasis occur in the stomach and rarely occur in the intestine. It is extremely rare for live larvae to break through the intestine into the mesentery and cause severe intestinal ischemia. Anisakiasis can be treated conservatively, because the larvae will die in approximately 1 week, but, sometimes, a serious condition can arise, as in this case. We report the first case of extraluminal anisakiasis in which a live Anisakis worm caused severe intestinal ischemia. Case presentation The patient was a 26-year-old woman who ate squid a week prior. She had abdominal pain and was admitted to our emergency department. On physical examination, abdominal guarding and rebound tenderness were present in her lower abdomen. Contrast-enhanced computed tomography showed ascites, the whirl sign, localized submucosal edema of the intestinal wall, and a dilated small bowel segment with edema. We suspected the strangulated small bowel obstruction based on the CT-scan findings. To rule out the strangulated small bowel obstruction, laparoscopic exploration was performed. Bloody ascites in the pouch of Douglas and severe inflammation in 20 cm of the ileum were observed. An Anisakis larva had perforated the intestinal wall and was found alive in the mesentery. The ileum had developed a high degree of ischemia, so the affected section was resected. Histopathological examination revealed that the Anisakis worm body was in the inflamed mesentery and caused a high degree of ischemia in the intestinal tract. The patient was discharged 9 days after surgery. Conclusions A living Anisakis larva punctured the mesentery of the small intestine, resulting in severe intestinal ischemia. As seen in this case, intestinal anisakiasis may cause serious symptoms, and a low threshold for performing diagnostic laparoscopy for the early diagnosis of bowel ischemia secondary to anisakiasis can be useful in determining the definite diagnosis and indications for resection.